Daily Optical Coherence Tomography Examinations after First Antivascular Endothelial Growth Factor Injections: An Interventional Case Series - Eduardo A. Novais; Emmerson Badaró; Flavio E. Hirai; Felipe Abdo Jorge; Paula Leal; Michel Eid Farah; Eduardo B. Rodrigues (Journal of Ophthalmology)
Purpose. To evaluate daily spectral-domain optical coherence tomography (SD-OCT) changes in naive-treatment patients with diagnosis of exudative age-related macular degeneration (AMD) treated with intravitreous bevacizumab (1.25 mg), during a 30-day follow-up period. Methods. In prospective, interventional study, SD-OCT was performed daily for 30 days after the first intravitreal injection. The baseline, initial-decrease, minimal, and final central retinal thicknesses (CRTs) were assessed. Results. Nine eyes of nine patients with neovascular AMD were enrolled. The mean baseline CRT was 625.3±182.5 μm, and the mean final CRT was 383.4±163.0 μm (mean difference, 206.1±167.6 μm), a difference that reached significance (P=0.006). After the first injection, the initial decrease in the CRT was seen as an average of one day after injection (mean CRT, 503.6±189.10 μm; P=0.0431). The speed of the reduction in the CRT tended to decrease by day 17. The mean CRT was 336.5±105.44 μm and the mean minimal CRT on day 30 was 320.75±96.38 μm. Conclusion. The CRT decreased early after the first injection. We observed a tendency for reductions in the speed with which the CRT decreased by day 17 after the first injection, which may affect retreatment regime.